ENHANCING SERVICE PERFORMANCE OF MICRO NOODLE SMES THROUGH KNOWLEDGE SHARING AND DIGITALIZATION INITIATIVES IN KUALA LUMPUR MALAYSIA - Supriadi , Yudi Nur; Huridi, Mohd Hanafia Bin; Rasyabi , Omar Rizki; Setiyani, Afri Dian; Mirza , Salsabila; Yulivan, Ivan (International Journal of Engagement and Empowerment (IJE2), 2025)
The Community Service International (CSI) program is a form of cross-border community service that aims to increase the capacity of MSMEs through a knowledge sharing and service digitization approach. This activity was carried out at one of the noodle-based culinary MSMEs in Malaysia which is still facing operational and technological constraints, such as the unavailability of QR codes for menus and orders, uncomfortable space layouts, the absence of a cash register so that transaction recording is still done manually, and an inefficient ordering flow because it uses a writing method on paper. Different from academic research that emphasizes theoretical analysis, PKM activities focus on solving real problems through socialization, technical direction, mentoring, and the creation of direct solutions that can be implemented by MSMEs. The results of the activity showed an increase in operational efficiency through the implementation of QR codes, the use of digital cashier applications, the improvement of business layouts, the preparation of simple SOPs, and an understanding of digital marketing. These findings show that knowledge-sharing-based Community Service International can be an effective approach in empowering culinary MSMEs in Malaysia to face modernization and digitalization challenges.